2023
DOI: 10.1001/jamadermatol.2022.6051
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lipid-Lowering Drugs With Risk of Psoriasis

Abstract: ImportanceLipid pathways have been implicated in the pathogenesis of psoriasis, and some lipid-lowering drugs, such as statins, are hypothesized to have disease-modifying properties. However, large population-level studies are scarce, and causal interpretation of results from traditional observational designs is limited by confounding.ObjectiveTo investigate the causal association between genetically proxied lipid-lowering drugs and psoriasis risk.Design, Setting, and ParticipantsThis 2-sample mendelian random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…After the Bonferroni correction, p < 0.0125 (0.05/4) was identified as significant, while associations with p ≥ 0.0125 and <0.05 were considered as suggesting significance 17 . Besides, we used odds ratios (ORs) with 95% confidence intervals (CIs) to present the effect estimates, which can be explained as the average variation in the outcome per log‐odds increase in the genetically predicted risk of the respective binary exposure 18 . Furthermore, comprehensive sensitivity analyses with several complementary MR methods, including weighted median estimator, MR‐Egger regression, and MR‐PRESSO were conducted to appreciate the stability of the outcome 19 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the Bonferroni correction, p < 0.0125 (0.05/4) was identified as significant, while associations with p ≥ 0.0125 and <0.05 were considered as suggesting significance 17 . Besides, we used odds ratios (ORs) with 95% confidence intervals (CIs) to present the effect estimates, which can be explained as the average variation in the outcome per log‐odds increase in the genetically predicted risk of the respective binary exposure 18 . Furthermore, comprehensive sensitivity analyses with several complementary MR methods, including weighted median estimator, MR‐Egger regression, and MR‐PRESSO were conducted to appreciate the stability of the outcome 19 .…”
Section: Methodsmentioning
confidence: 99%
“…17 Besides, we used odds ratios (ORs) with 95% confidence intervals (CIs) to present the effect estimates, which can be explained as the average variation in the outcome per log-odds increase in the genetically predicted risk of the respective binary exposure. 18 Furthermore, comprehensive sensitivity analyses with several complementary MR methods, including weighted median estimator, MR-Egger regression, and MR-PRESSO were conducted to appreciate the stability of the outcome. 19 Additionally, MR-PRESSO was employed to detect potential outlier instrument (p < 0.05), which was removed stepwise to decrease the horizontal pleiotropy effect.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…13 The association between lipid-lowering drug targets and autoimmune diseases has been investigated using MR approaches, and Zhao et al found that PCSK9 is associated with the pathogenesis of psoriasis and its inhibition is associated with a reduced risk of psoriasis. 14 However, less has yet investigated the potential association between PCSK9 and SLE. Therefore, the present study used the MR method to try to determine whether there is genetic evidence for an effect of PCSK9 inhibition on SLE.…”
Section: Mendelian Randomization (Mr) Analysis Allows Researchers Tomentioning
confidence: 99%
“…To preclude genetic confounders, we sought corroboration of the genetic link via Bayesian colocalization analysis. 5 MR results indicated no causal link between acne and COVID-19 susceptibility or severity but a significant association with increased COVID-19 hospitalization risk (odds ratio = 1.09, 95% confidence interval: 1.02-1.16, p = 0.017) without heterogeneity and pleiotropy (Supporting Information S1: Tables 2 and 3). Reverse MR analyses revealed no causal connection between COVID-19 factors and acne (Figure 2).…”
mentioning
confidence: 98%